Conselhos gestores e empoderamento político feminino : uma análise da trajetória política de parlamentares brasileiras de 1987 a 2016 - Proença, Maressa Aires de (2017)
Anxious to establish critical reflections on the issue of women as a political agent, this research aims to situate the importance of participation in e Public Policy Administrative Councils as a political empowerment mechanism relevant to understanding the possibilities and limitations in promoting participation women in politics. Thus, the research is organized around the raising of standards and variations found in the political trajectory of elected parliamentarians in the last eight legislatures that they are: 48th Legislature (1987-1991); 49th Legislature (1991-1995); 50th Legislature (1995-1999); 51st Legislature (1999-2003); 52nd Legislature (2003-2007); 53rd Legislature (2007-2011); 54th Legislature (2011-2015) and 55th Legislature (2015-2019), this historical period was given in order to examine the period between the National Constituent Assembly of 1987, which aimed to draw up a democratic constitution for Brazil after 21 years under the military regime, in which the Public Policy Administrative Councils were inaugurated, to the present, where we observe an increasing participation in these spaces of democratic representation. Here we propose a comparative analysis of data from these parliamentarians over the year of participation in the Management Board and the year of his election, the themes developed throughout its term and themes during his participation in Public Policy Administrative Councils and also his party origin, the number of times it has been re-elected and personal profile (age, occupation, marital status). Thus, we analyze the implications and impacts of participation in Public Policy Administrative Councils in the political trajectory of those who, through cooperative channels of power, reached the numerical channel power .